Ciudad, teatro, mapas - Alonso Miguel, Álvaro (Revista de Filología Románica, 2009)
The present article is centred on the study of the analogical relations established between the city and the cosmos or the world in diverse texts of the Spanish Golden Age, by means of the comparison between the urban plan and the world map. The importance of this motive in the theatre of the time is brought to light remarking Lope’s braking of the unity of space law. Therefore, the scenery of a dramatic performance may contain in itself the hole world. Other aesthetic practices, such as the ones in Gongora’s Soledades, the conceptist style, some decorative objects, tapestries, the map or painting can also serve as mechanisms to represent an abridged world. Maps and painting are paradigmatic procedures regarding the reduced reproduction of space and, therefore, become the most used metaphors to refer to the concept of the city as a microcosm.